2020
DOI: 10.3389/fped.2020.00039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Diagnostic Therapeutic Educational Pathway for Asthma Management in Children and Adolescents

Abstract: Background: Limited evidence exists for the effectiveness of educational programs that improve pediatric asthma control in real-world settings. We aimed to assess the impact of a diagnostic, therapeutic, and educational pathway (DTEP) for asthma management in children and adolescents attending an asthma referral center.Methods: This is a retrospective population-based cohort study, including two groups of patients with asthma, aged 6-17 years and residing in the Local Health Authority (LHA) of Brescia, Italy: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…38 Previously it was emphasized that establishing asthma action plans are necessary in order to minimize the problems of families. 24,[39][40][41][42][43] In conclusion, this is the first study that examines in detail the experience of mothers with children with asthma and the findings of the current study demonstrated the significant impact mothers emotional problems have on the parents' everyday life and the importance of health professionals' knowledge to identify and support mothers with these conditions. Acknowledging these experiences and their implications will improve interventions and support by health professionals as they assist families.…”
Section: Discussionmentioning
confidence: 58%
“…38 Previously it was emphasized that establishing asthma action plans are necessary in order to minimize the problems of families. 24,[39][40][41][42][43] In conclusion, this is the first study that examines in detail the experience of mothers with children with asthma and the findings of the current study demonstrated the significant impact mothers emotional problems have on the parents' everyday life and the importance of health professionals' knowledge to identify and support mothers with these conditions. Acknowledging these experiences and their implications will improve interventions and support by health professionals as they assist families.…”
Section: Discussionmentioning
confidence: 58%
“…Several previous randomized clinical trials have shown not only that asthma control can be substantially improved by self-management training, a core component of which is patient education, but also that educational and behavioral interventions can achieve positive results in asthma control in children and adults (10,11). We have previously documented a favorable impact of our DTEP on asthma control and asthma-related outcomes among children and adolescents aged 6-17 years (12)(13)(14)(15)(16). Since no previous study had evaluated the impact of a Diagnostic Therapeutic Educational Pathway (DTEP) on asthma control among children of less than 6 years so far, the present study, to our knowledge, is the rst to do so.…”
Section: Discussionmentioning
confidence: 77%
“…The Center "Io e l'Asma" is an outpatient pediatric asthma center at the University of Brescia, which provides a Diagnostic Therapeutic Educational Pathway (DTEP), designed to obtain and maintain control of wheezing by focusing on child and family autonomy and relying on a strong collaboration between specialists and primary care physicians, where we organized several meetings to share the DTEP following the GINA guidelines, during the last fteen years (12)(13)(14)(15)(16).The DTEP consists of three specialist evaluations at the Center, with an 8-12 weeks' interval between them, and two follow-up visits at 6 and 12 months after the last evaluation. After each specialist's evaluation, the child is referred to his/her primary care physician for documenting the symptoms control by clinical evaluation and adjusting therapy for 6-8 weeks based upon the degree of wheezing and respiratory compromise.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Однако такой подход может привести к диагностической ошибке: положительный или отрицательный ответ на лечение, не является надежным тестом, так как причины положительного ответа включают эффект плацебо (обычно очень высокий в исследованиях по ингаляционной фармакотерапии), естественную спонтанную изменчивость симптомов, наличие другого, отличного от БА кортикостероид-чувствительного респираторного заболевания. И наоборот, отрицательный ответ может быть связан с плохим соблюдением регулярной терапии, неверной техникой использования ингалятора или прогрессированием заболевания [7,8].…”
unclassified